Comparison of quantum dot-binding protein tags: Affinity determination by ultracentrifugation and FRET - Werwie, Mara; Fehr, Niklas; Xu, Xiangxing; Basché, Thomas; Paulsen, Harald (Biochimica et biophysica acta, 2014)
Hybrid complexes of proteins and colloidal semiconductor nanocrystals (quantum dots, QDs) are of increasing interest in various fields of biochemistry and biomedicine, for instance for biolabeling or drug transport. The usefulness of protein-QD complexes for such applications is dependent on the binding specificity and strength of the components. Often the binding properties of these components are difficult and time consuming to assess. In this work we characterized the interaction between recombinant light harvesting chlorophyll a/b complex (LHCII) and CdTe/CdSe/ZnS QDs by using ultracentrifugation and fluorescence resonance energy transfer (FRET) assay experiments. Ultracentrifugation was employed as a fast method to compare the binding strength between different protein tags and the QDs. Furthermore the LHCII:QD stoichiometry was determined by separating the protein-QD hybrid complexes from unbound LHCII via ultracentrifugation through a sucrose cushion. One trimeric LHCII was found to be bound per QD. Binding constants were evaluated by FRET assays of protein derivatives carrying different affinity tags. A new tetra-cysteine motif interacted more strongly (Ka=4.9±1.9nM(-1)) with the nanoparticles as compared to a hexahistidine tag (His6 tag) (Ka~1nM(-1)). Relative binding affinities and binding stoichiometries of hybrid complexes from LHCII and quantum dots were identified via fast ultracentrifugation, and binding constants were determined via FRET assays. The combination of rapid centrifugation and fluorescence-based titration will be useful to assess the binding strength between different types of nanoparticles and a broad range of proteins.